Evaluasi Kebijakan Pemberian Asimilasi dan Integrasi Terhadap Narapidana dan Anak Dalam Rangka Pencegahan Penyebaran Covid-19 - Afifah; Weni Rosdiana (Universitas Negeri Surabaya, 2023)
In order to stop the spread of the Covid-19 virus, the Indonesian Ministry of Law and Human Rights has issued a strategy to assimilate and integrate prisoners. When a prisoner meets the standards as outlined in the relevant rules, assimilation is given. Adult and juvenile inmates are guided towards assimilation to give them the opportunity to be able to socialize with society. In contrast to the integration carried out by releasing prisoners who have met the requirements according to applicable regulations. In preventing and controlling the spread of Covid-19, the policy of the Minister of Human Rights of the Republic of Indonesia No. 10 of 2020 concerning Assimilation Requirements and Integration Rights of Prisoners and Children has caused debate. This was chosen taking into account the sensitivity of the spread of Covid-19 in overcrowded prisons. In this study, descriptive qualitative research techniques were used with the literature study methodology. The purpose of this study is to ascertain how the policy is assessed. The findings of this study show that the government's actions are quite appropriate, as evidenced by the fact that the Covid-19 virus has not spread widely.